DIGITALISASI PEMASARAN PADA UMKM EMPING MELINJO DI DUSUN MERGAN YOGYAKARTA PADA MASA PANDEMI COVID-19 - Alien Akmalia; Rita Kusumawati (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The target partner in this community service activity is Ms. Ani's Micro, Small and Medium Enterprises (MSMEs). This MSME is located in Mergan, Minggir District, Sleman, Yogyakarta. The problems faced by partners are in the marketing aspect, especially during the current pandemic. The purpose of this community service is assisting to solve the problems faced by ‘emping melinjo MSMEs’ in the marketing aspect, so they can be survive the COVID-19 pandemic that hit almost all part of the world, including Indonesia. The method used in the implementation of this service consists of: observation, interviews, discussions, demonstrations, hands-on practice, training and mentoring. The results of this service program include: (1) Target partner has attractive product photos; (2) Target partner owned Instagram social media to introduce and market their products; (3) Target partner is able to manage Instagram social media. The results of this community service can be a reference for the next community service implementers, especially in the field of digital marketing for MSMEs.